Measuring The Level of Knowledge and Awareness of The People in Jambi Province Pay Zakat Through E-Commerce - Paulina Lubis; Rafiqi Rafiqi; Ary Dean Amri; Fitri Widiastuti (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: This paper examines the level of knowledge and awareness of the Jambi province community in issuing zakat through the e-commerce payment system.Design/Method/Approach: This study uses descriptive analysis by applying a quantitative approach to obtain information and collect the required data through google forms. Observation and literature study were also applied to expand the secondary data. The method is carried out to see the model of knowledge, awareness people pay zakat through e-commerce. Can it speed up the collection and distribution of zakat funds to people in need?Findings: The results showed that the level of knowledge and public awareness distribute zakat through e-commerce had a significant positive effect on the acceleration in the collection of zakat funds. The greater the level of knowledge and public awareness in the use of e-commerce, it can help accelerate the collection and distribution of zakat funds in Jambi Province.Originality/Values: The main contribution of this research is the existence of payment services and distribution of zakat funds by e-commerce which is very helpful and fosters awareness and knowledge of the Muslim community who wants to pay zakat without having to meet face to face, and Islamic law remains valid